The Rohingya Muslim in the Land of Pagoda - Winarni, Leni (JAS (Journal of ASEAN Studies), 2017)
Regarding Southeast Asia as a multi-ethnics region, this paper attempts to examine about why Buddhist Community turns into religious violence against Rohingyas in the State of Rakhine (formerly known as Arakan). Through understanding the triggers of conflicts, this paper applies historical perspective to analyze why ethnic-religious conflict occur nowadays between Buddhist and Rohingya in Myanmar. This paper also discusses how the influence of history has constructed the government’s policy under military regime to exclude Rohingya. However, the ethno-religious conflict is either an indication of a weak state or failure state in managing diversity.Key words: Ethnic-